ANALYSIS OF THE NATURE, GROUPING AND IDENTIFICATION CRITERIA OF LARGE TAXPAYERS (International Conference on Economics, Finance, Banking and Management, 2025)
This article analyzes the foreign experience of implementing the tax administration of large taxpayers, as a result of this analysis, issues of improving the tax legislation of the Republic of Uzbekistan, a proposal for further improvement of the tax administration of large taxpayers and recommendations are developed.